Bagaimana Jika Ki Hajar Dewantara Mengajar Pendidikan Jasmani? - Hari Amirullah Rachman (Jurnal Pendidikan Jasmani Indonesia, 2005)
In the learning process of the physical education at the elementary school,actually there are many thoughts of Ki Hajar Dewantara, the national education’sfather, still relevant to and necessary to contemplate to be applied by the physicaleducation teachers.His thoughts, such as independence principality as the educational principality, arecharacterizing the self-supporting, productive and creative, and also high-disciplinedhuman being. Implicitly the thoughts are in accordance with the target of the physicaleducation that is to develop discipline, skill, fitness, reasoning, and social emotion.If Ki Hajar Dewantara becomes a physical education teacher, there will be no doubtthat his thoughts will be used as main foundations for efficiently and effectively physicaleducation learning process, to reach the targets of national education.Keyword: Ki Hajar Dewantara, Physical Education, Elementary School teacher.